Power-Assisted Scissors Reduce Adductor Pollicis Muscle Fatigue: A Comparative Study in Female College Students - Kohei Koizumi; Kumiko Sasao; Yoshihiro Senju; Toyohiro Hamaguchi (Applied Sciences)
Hand fatigue commonly occurs in repetitive tasks, such as cutting with scissors, leading to discomfort, reduced productivity, and musculoskeletal disorders. Recent advances in assistive technology have introduced power-assisted scissors to reduce the muscular load. Pinching and grasping mainly involve the adductor pollicis muscles of the hand. Measuring the electromyographic (EMG) activity of these muscles provides valuable insights into the muscular effort required for such tasks. Studies have indicated that power-assisted devices can effectively reduce muscle strain and fatigue. However, research on the effect of power-assisted scissors on adductor pollicis muscle activity is limited. This study examines the differences in adductor pollicis muscle activity using power-assisted scissors versus traditional scissors. The experiment consisted of 20 participants performing a scissor manipulation task with and without power assistance. Frequency analysis of the adductor pollicis muscle EMG data indicated that scissors with power assistance significantly reduced muscle fatigue (95% confidence interval, 10.705 [4.523–19.751], p < 0.01, η2 = 0.01). Understanding the efficacy of power-assisted scissors has significant implications for occupational health—particularly in professions that involve extensive manual cutting, such as tailoring and hairdressing. This study can contribute to the design of ergonomic tools that enhance comfort and reduce musculoskeletal disorder risks.